Profile of Determinants of Life Satisfaction of Housewives Who Work - Nadya Dwi Dara Mairen; Netrawati Netrawati (Jurnal Neo Konseling, 2020)
This research is motivated by the phenomenon of housewives who work to earn extra income for the family, the recognition of others and their assessment of the dual role they lead in living life. This study aims to describe the determinants of life satisfaction of working housewives in terms of: (1) life opportunities, (2) the process of life events (3) the flow of experience, and (4) the process of evaluating life. This type of research is quantitative descriptive research . With a sample of working housewives who reside in the Housing of Koto Baru, Kec. Kubung, Kab. Solok as many as 179 people were selected using the Simple Random Sampling technique. The research instrument was a questionnaire determining the satisfaction of the lives of working housewives. Data were processed using descriptive statistical analysis techniques. The results of the study revealed that: (1) the determinants of life satisfaction of housewives who work from the aspect of life opportunities are in the quite satisfied category (33.52%) (2) the aspects of the life process process are at the moderately satisfied category (35.20%) (3) in the aspect of experience flow are in the quite satisfied category with 24.25%, and (4) and the aspect of the life evaluation process is in the quite satisfied category (37.43%).